(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
This paper is a didactic introductory text to the verbal behavior theme, in a behavioral-analytic perspective. The verbal behavior is characterized as operant behavior, but there are some differences between the verbal behavior and the others operant behaviors. Some basics categories of verbal behavior are refereed at the end of the paper.